2017
DOI: 10.4103/0970-1591.194785
|View full text |Cite
|
Sign up to set email alerts
|

Double breasting spongioplasty in tubularized/tubularized incise plate urethroplasty: A new technique

Abstract: Introduction:The main disadvantage of currently described techniques of spongioplasty is superimposition of 3 suture lines (neourethra, spongioplasty, and skin closure) which is likely to increase the chances of a fistula. We describe and evaluate the results of a double breasting spongioplasty in urethroplasty.Methods:A prospective study of 60 primary hypospadias was undertaken by double breasting spongioplasty from August 2012 to March 2014. Mobilization of the urethral plate and the spongiosum is done by cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Bhat et al, 26 using the double-breasting spongioplasty modification, reported a very low incidence of urethrocutaneous fistula, approximately 1.66%. This rate is significantly lower than what is typically reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Bhat et al, 26 using the double-breasting spongioplasty modification, reported a very low incidence of urethrocutaneous fistula, approximately 1.66%. This rate is significantly lower than what is typically reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Bhat et al . [8] describe another technique where they “double-breast” the spongiosum over the urethral closure plate, avoiding an overlapping suture line. In a prospective study on sixty patients with a mean age of under 4 years, they report a single fistula.…”
Section: Double-breasting the Spongiosum In Urethroplastymentioning
confidence: 99%